2022
DOI: 10.1101/2022.12.28.522104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disease-modifying effects of Vincamine supplementation inDrosophilaand human cell models of Parkinson’s disease

Abstract: Parkinson's disease (PD) is an incurable neurodegenerative disorder caused by the selective loss of dopaminergic neurons in thesubstantia nigra pars compacta. Current therapies are only symptomatic, and are not able to stop or delay its progression. In order to search new and more effective therapies, our group carried out a high-throughput screening assay, identifying several candidate compounds able to suppress motor defects inDJ-1βmutant flies (aDrosophilamodel of familial PD) and to reduce oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…These contain anti-inflammatory properties and could help reduce inflammation in the brain that is involved in PD. Studies have shown that taking omega-3 supplements may help with the motor symptoms of PD [52]. Treatment with docosahexaenoic acid enhanced antioxidant defence, reduced the death of dopaminergic neurons, and increased motor performance in mice challenged with MPTP.…”
Section: Omega-3-polyunsaturated Fatty Acidsmentioning
confidence: 99%
See 4 more Smart Citations
“…These contain anti-inflammatory properties and could help reduce inflammation in the brain that is involved in PD. Studies have shown that taking omega-3 supplements may help with the motor symptoms of PD [52]. Treatment with docosahexaenoic acid enhanced antioxidant defence, reduced the death of dopaminergic neurons, and increased motor performance in mice challenged with MPTP.…”
Section: Omega-3-polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…As a primary polyphenol in green tea, epigallocatechin-3gallate (EGCG) is known to be beneficial for those who have PD since it is well known for its properties of being antiinflammatory, antioxidant and neuroprotective. According to an in vitro study, EGCG and its metabolites can pass through the blood-brain barrier and cause neuritogenesis in the brain parenchyma [52]. The preventive effect of EGCG against dangerous DA metabolites is contributed by its catechol-like structure.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
See 3 more Smart Citations